BIOMETRY AND EDUCATON - HAMBALÍK, Alexander (Trends in education, 2009)
The article introduces basic information of used new, modern ICT technology, which work on a base biometrics, in education area.
Keywords: biometry; ICT; components on a base biometrics; practice use biometrics in the school area.